2021
DOI: 10.1055/s-0041-1732815
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Syrian Population’s Knowledge, Attitudes, and Practices Regarding Antibiotic Usage

Abstract: Background Antibiotic resistance is a serious public health threat that results mainly secondary to antibiotics misuse. The present study aimed to determine the knowledge, attitude, and practice toward antibiotic use among the Syrian population. Methods This cross-sectional study was conducted at the outpatient clinics of two major hospitals in Damascus, Syria. Applying a random convenience sampling, data were collected in a 1-week period by interviewing participants using a structured questionnaire, which tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…There were statistically significant differences in health insurance status. A study finds significant differences in residents' attitudes towards antibiotic use and whether they have medical insurance [86]. Those who had heard of antibiotic resistance and those who were worried about antibiotic resistance had higher self-efficacy scores than those who had not heard of antibiotic resistance.…”
Section: Analysis Of Differences In Self-efficacy Of General Informat...mentioning
confidence: 99%
“…There were statistically significant differences in health insurance status. A study finds significant differences in residents' attitudes towards antibiotic use and whether they have medical insurance [86]. Those who had heard of antibiotic resistance and those who were worried about antibiotic resistance had higher self-efficacy scores than those who had not heard of antibiotic resistance.…”
Section: Analysis Of Differences In Self-efficacy Of General Informat...mentioning
confidence: 99%
“…Unfortunately, a large number of participantswere using antibiotics improperly for a varietyof reasons, including a lack of resources andinstruction. [52] Palestine In Palestine, a case study was conducted for the Palestinian pharmacist out of 155 pharmacists showed that 77•0% or 119 encounters of doctors prescribed an unnecessary antibiotic medication, 82•6% or 128 were from patients who were mad and demanded without prescription and 60•8% or 94% given the medication without prescription. [55] alestine has a high percentage of using self-education in antibiotics which was reported by 98% of students surveyed at An-Najah National University.…”
Section: Jordanmentioning
confidence: 99%
“…Globally, a study done in Syria on knowledge, attitude and practice on antibiotic usage stated that unchecked, antibiotic resistance can halt and potentially reverse decades of medical progress with severe repercussion on patients' outcome and healthcare expenditure both on an individual and societal level According to a study in Malta, approximately 700,000 deaths are registered from antibiotic resistant infections every year. This AMR related mortality is predicted to rise to 10 million people per year by 2050 (Altorkmani, et al, 2021) In Syria, although there are regulations prohibiting sale of antibiotics without prescription, most pharmacies do not adhere to these regulations and this is evidenced by a study conducted in Aleppo, Syria which reported that 85.5% of pharmacies in the city prescribe antibiotics to patients without prescription (Altorkmani et al, 2021). In Africa, antibiotics are among the commonest medicines used.…”
Section: Introductionmentioning
confidence: 99%